2002
DOI: 10.1124/dmd.30.7.814
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclophosphamide with and without Dexamethasone on Cytochrome P450 3A4 and 2B6 in Human Hepatocytes

Abstract: ABSTRACT:The purpose of this study was to characterize the concentrationresponse effects of cyclophosphamide (CPA) with and without dexamethasone (DEX; 10 M) on the expression of CYP3A4 and CYP2B6 in cultured human hepatocytes at concentrations representative of standard-and high-dose CPA therapy (25 to 750 M). CPA produced concentration-dependent increases in CYP3A4 and CYP2B6 activity and immunoreactive protein that peaked at 250 and 125 M, respectively, and declined thereafter. The inductive effect of CPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 30 publications
6
56
0
Order By: Relevance
“…Remarkably, ifosfamide had a greater capacity to induce CYP3A4 compared to cyclophosphamide, which is an isomer of ifosfamide. Lindley et al [22] showed that cyclophosphamide is able to activate PXR at a concentration >100 M in vitro, which is conWrmed by our results. Clinical proof for our observations that the other anticancer drugs, paclitaxel, docetaxel, Xutamide and erlotinib, have the potential to cause pharmacokinetic drug-drug interaction is not yet known and should be further investigated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, ifosfamide had a greater capacity to induce CYP3A4 compared to cyclophosphamide, which is an isomer of ifosfamide. Lindley et al [22] showed that cyclophosphamide is able to activate PXR at a concentration >100 M in vitro, which is conWrmed by our results. Clinical proof for our observations that the other anticancer drugs, paclitaxel, docetaxel, Xutamide and erlotinib, have the potential to cause pharmacokinetic drug-drug interaction is not yet known and should be further investigated.…”
Section: Discussionsupporting
confidence: 91%
“…Paclitaxel [10], cyclophosphamide [22] and tamoxifen [11] were already known to induce CYP3A4 expression via activation of PXR and our data conWrm these results. However, in contrast to other studies [10,25] we observed a small, but signiWcant CYP3A4 reporter activity after treatment with docetaxel.…”
Section: Discussionsupporting
confidence: 87%
“…Compounds that achieved significantly greater than 30% of RIF-normalized hPXR activation of CYP3A4 reporter gene expression at one or more concentrations were classified as moderate to strong activators of hPXR, whereas drugs exhibiting less than 30% were classified as weak or nonactivators of hPXR. Consistent with previous reports, ART, CPA, LOV, MET, MEV, RU486, NIC, NIF, OMP, RES, SIM, and TGZ were classified as moderate to strong hPXR activators (fold activation Ͼ 30% of RIF response) (Drocourt et Kocarek et al, 2002;Lindley et al, 2002;Raucy, 2002;Burk et al, 2005). To our knowledge, this is the first demonstration of hPXR activation by CPZ.…”
Section: Resultssupporting
confidence: 76%
“…By combining results from the hPXR-and hCAR3-based reporter gene assays, these inducers were classified as hPXR, hCAR, or hPXR/hCAR dual activators. Our results demonstrate that CMZ, EFV, and NVP induce CYP2B6 and CYP3A4 preferentially through hCAR and that hCAR3 represents a sensitive tool for in vitro prediction of chemical-mediated human CAR activation.CYP3A4 and CYP2B6 are induced at the mRNA, protein, and activity levels by the same compounds, including rifampin, phenobarbital, clotrimazole, cyclophosphamide, calcium channel antagonists, HMG-CoA reductase inhibitors, and thiazolidinediones (Drocourt et al, 2001;Kocarek et al, 2002;Lindley et al, 2002;Sahi et al, 2003;Faucette et al, 2004). Coinduction of these enzymes is mediated through transcriptional activation of the corresponding genes by the nuclear receptors pregnane X receptor (PXR) and constitutive androstane receptor (CAR), which are capable of binding to the same response elements in the promoter regions of the CYP3A4 and CYP2B6 genes (Goodwin et al…”
mentioning
confidence: 99%
See 1 more Smart Citation